Analysis of Congenital Heart Defect in Pakistan - Jabar Imran, Abdul Lateef, Salman Raza, Muhammad Zarrar Arif Butt (Pakistan Journal of Medical & Health Sciences, 2022)
Background and objectives: While the defect has been studied extensively in Pakistan, there have been just a few of research focusing on KPK populations. Because of this, the goal of this study was to identify neonatal congenital heart disease in Pakistani children. Methodology: This cross sectional study was conducted in Sheikh Zayed Medical College during June 2021 to November 2021. Echocardiography was used to diagnose congenital heart disease in 1683 neonates who reported to the outpatient department (OPD) with a variety of ailments. Results: Out of 1683 babies, a total of 303 (or 18%) had a congenital heart condition. It was found that 62.5 per cent of people infected with the virus were men, while 37.5% of them were women. 78 per cent of the cases included infants between the ages of one and three months. Patients described a variety of symptoms they were experiencing. Asthma, pneumonia, and cyanosis were the most prevalent causes of death (4 per cent). The great majority of patients had the cyanotic congenital cardiac disease (98 per cent). (77.9 per cent), followed by PDA (11.5 per cent), ASD (7.9 per cent), TOF (0.9 percent), and aortic stenosis (0.9 per cent) were the most common congenital heart defects observed in the study. (Aortic stenosis was the least common disease) (2.2 per cent). Conclusion: To detect cardiac murmurs in our newborn population, the doctors in our paediatric outpatient clinics must increase their performance. This may result in a significant decrease in sales.